Some further ideas on a double-obverse bronze of the Constantinian period from the Antioch excavations - Caza, Shawn (KOINON: The International Journal of Classical Numismatic Studies, 2019)
In Concordia Disciplinarum: Essays on Ancient Coinage, History and Archaeology in Honor of William E. Metcalf (Numismatic Studies 38), Alan M. Stahl and Rafail Zoulis describe a Constantinian bronze coin found in the 1937 excavations at Daphne, near Antioch, which has the laureate, draped and cuirassed bust of Constantine on both sides.